2013
DOI: 10.1007/s12011-013-9678-8
|View full text |Cite
|
Sign up to set email alerts
|

Cerium Oxide Nanoparticles Protect Endothelial Cells from Apoptosis Induced by Oxidative Stress

Abstract: Oxidative stress is well documented to cause injury to endothelial cells (ECs), which in turn trigger cardiovascular diseases. Previous studies revealed that cerium oxide nanoparticles (nanoceria) had antioxidant property, but the protective effect of nanoceria on ROS injury to ECs and cardiovascular diseases has not been reported. In the current study, we investigated the protective effect and underlying mechanisms of nanoceria on oxidative injury to ECs. The cell viability, lactate dehydrogenase release, cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
68
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(76 citation statements)
references
References 46 publications
7
68
0
1
Order By: Relevance
“…Thus, current study has shown in animal model that nanoceria could reduce visceral adipose tissue mass effectively, confirming recently published data [21].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, current study has shown in animal model that nanoceria could reduce visceral adipose tissue mass effectively, confirming recently published data [21].…”
Section: Resultssupporting
confidence: 92%
“…Recent evidence suggests that NDC slows the progression of degeneration of retina [18], has antioxidant properties in brain tissues [19] fibroblasts of human skin [20] and endothelial cells [21]. Antioxidant properties of nanoceria in digestive tract have not been deeply studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have been performed to evaluate the adverse effect of CeO 2 NPs on environment and human health, they are not providing proper conclusion. CeO 2 NPs have been reported to act as cellular antioxidants with colocalizations inside mitochondria, lysosomes, endoplasmic reticulum, nucleus, and cytoplasm using keratinocyte model systems [14, 15]. However, the study lacked genotoxicity assessment of these particles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CeO 2 -NP enter into the cells promoting the removal of oxidative molecules and cell longevity (Kong et al 2011). This free radical-scavenging property has been described in different studies reporting gastrointestinal (Colon et al 2010), breast (Tarnuzzer et al 2005), neuronal (Schubert et al 2006), and endothelial (Chen et al 2013) cell protection in in vitro and in vivo studies.…”
Section: Introductionmentioning
confidence: 58%